Eustachian Tube Function in Patients Receiving Continuous Positive Airway Pressure Treatment for Sleep Apnea Syndrome - AKSOY, FADLULLAH; AKSOY, Fadlullah; YILDIRIM, YAVUZ SELİM; Yildirim, YAVUZ SELİM; ÖZTURAN, ORHAN; Ozturan, ORHAN; VEYSELLER, Bayram; Cuhadaroglu, Caglar (My University, 2010)
Objective: We evaluated eustachian tube (ET) function in patients using continuous positive airway pressure (CPAP).